Pericardial effusion after pediatric hematopoietic cell transplant. (7th March 2013) - Aldoss, Osamah; Gruenstein, Daniel H.; Bass, John L.; Steinberger, Julia; Zhang, Yan; DeFor, Todd E.; Tolar, Jakub; Verneris, Michael R.; Orchard, Paul J.
Abstract PE can occur following HCT. However, the incidence, etiology, risk factors, and treatment remain unclear. We performed a retrospective study evaluating 355 pediatric recipients of HCT treated at a single institution between January 2005 and August 2010. No cases of PE were identified in the autologous HCT (auto‐HCT) recipients (0/43), while 19% (57/296) of allogeneic HCT (allo‐HCT) developed PE. Among the 57 PE patients, 40 (70%) were males; the median age at transplantation was 6.6 yr (0.1–17.3 yr). Thirty‐six patients (63%) had significant PE with 23 patients (40%) treated by pericardiocentesis, and 19 (33%) experiencing recurrent PE. OS rates for patients who developed PE were 84% at 100 days and 65% at three yr after HCT. Risk factors associated with PE on multivariate analysis included myeloablative conditioning (p = 0.01), delayed neutrophil engraftment (p < 0.01), and CMV + serostatus of the recipient (p = 0.03). Recipients with non‐malignant diseases were significantly less likely to die after development of PE (p = 0.02 and 0.004 when comparing with standard and high‐risk diseases, respectively). In summary, PE is a common and significant complication of pediatric allo‐HCT. Prospective studies are needed to better determine the etiology and optimal method of PE treatment after HCT.